Evaluation of behaviour of Lachancea thermotolerans biocontrol agents on grape fermentations - Nally, Maria Cristina (2018)
Previous researches have showed that Lachancea thermotolerans strains RCKT4 and RCKT5 inhibited the growth of Aspergillus. However, currently, there are no data on their nutritional preferences, as a possible substrate competitor against Saccharomyces cerevisiae, and their effects on fermentation. In this work, we observed that the biocontrol yeasts and S. cerevisiae BSc203, based on the utilization of 16 carbonate sources, revealed significant differences in the nutritional profile (biocontrol yeasts NS:0·25, BSc203 NS:0·56). Lachancea thermotolerans strains did not occupy the same niche as that of BSc203 (NOI:0·44). The biocontrol agents and BSc203 presented similar competitive attitude in terms of the sugar, ethanol and sulphite tolerances. During fermentation, the biocontrol yeasts were found to tolerate up to 12% v/v ethanol, 250 mg ml−1 of total SO2 and 30° Brix sugar. In mixed cultures, L. thermotolerans strains did not negatively affect the growth of BSc203 and the wine quality, except when RCKT4 was initially inoculated at a high proportion in the mixed culture 1MSK4 (1%BSc203/99%RCKT4), resulting in a lower production of CO2 and ethanol, in comparison with pure BSc203. RCKT5, at a high proportion, in 1MSK5 (1%BSc203/99%RCKT5) presented promising oenological properties. This fermentation showed lower acetic acid contents and higher total acidity than pure BSc203. Significance and Impact of the Study: Generally it is not evaluated if the biofungicide yeasts sprayed on vegetables alter the quality of the fermented products. This work focused on the importance of assessing the possible effects of yeast-based fungicides used in vineyards on grape fermentation, especially on Saccharomyces cerevisiae growth. In this context, the competition between biofungicide yeasts and S. cerevisiae under winemaking conditions is investigated.